SIKAP MEDIA ASING DALAM MENYOROTI KASUS PENISTAAN AGAMA AHOK (Foreign Media Attitude to Highlight Ahok’s Blasphemy Case) - Retno Hendrastuti (Balai Bahasa Sulawesi Selatan, 2019)
AbstractIn 2017, Ahok’s Blasphemy Case (ABC) got big attention from foreign mass media. Then, how did the foreign mass media take a position broadcasting it? It is a qualitative descriptive study that aims to describe the attitude and its object of foreign mass media’s ABC news texts. The study used lexis and phrases that reflecting attitude as data. The data were collected from ABC Indonesian news texts from three foreign mass media of Deutsche Welle, BBC, and VOA. The data were analyzed with the appraisal approach to finding out their attitude toward ABC. The study result showed that there were three kinds of attitudes: positive and negative affects, judgements, and appreciations. The positive affects were to evaluate participants’ attitudes who want to create comfort conditions. The negative affects implied fear of ABC as the source of stress and anxiety for Indonesian. Then, the positive personal judgements showed the need for a safe and fair state for ABC and the negative personal judgements showed the stressful aspect. The positive moral judgements were about Ahok’s cooperative attitudes. The negative moral judgements were directed to the action of attacking certain people or ideologies. Then, the appreciations focused on evaluating things, people who supported a conducive situation. The negative appreciations were associated with ABC that create chaos situation. However, the domination of positive attitudes were about ABC showed support to finish ABC fairly and peacefully.AbstrakPada 2017, kasus penistaan agama Ahok (KPAA) mendapat perhatian besar dari media massa asing. Lalu, bagaimana media massa asing menyoroti kasus ini? Penelitian ini adalah penelitian deskriptif kualitatif yang bertujuan mendeskripsikan sikap dan objek sikap media massa asing pada teks berita KPAA. Data berupa leksis sikap diambil dari teks berita tiga media massa asing, yaitu Deustche Welle, BBC, dan VOA yang berbahasa Indonesia. Data dianalisis dengan pendekatan appraisal untuk mengetahui sikap mereka terhadap KPAA. Hasil penelitian menemukan tiga jenis sikap, yaitu perasaan, penilaian, dan apresiasi yang bermuatan positif dan negatif terkait KPAA. Perasaan positif ditujukan untuk partisipan yang ingin menciptakan kondisi yang menentramkan. Perasaan negatif mengisyaratkan ketakutan terhadap KPAA sebagai sumber tekanan dan kecemasan bagi bangsa Indonesia. Penilaian personal positif menunjukkan keinginan akan situasi negara aman dan adil dan penilaian personal negatif yang terkait dengan hal-hal yang menciptakan ketegangan. Penilaian moral positif terkait dengan perilaku kooperatif Ahok. Penilaian moral negatif tertuju pada tindakan menyerang orang atau ideologi tertentu. Apresiasi positif fokus mengevaluasi benda atau orang yang mendukung situasi kondusif. Apresiasi negatif dikaitkan dengan situasi gaduh di masyarakat. Dominasi sikap positif menunjukkan dukungan untuk penyelesaian KPAA dengan adil dan damai.